PENERAPAN MODEL PJBL DENGAN BERBASIS PERTANIAN INDUSTRIALUNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KREATIF SISWA TEMA WIRAUSAHA - Purnami, Ita; Safitri, Dian Indah (UNIVERSITAS MUHAMMADIYAH METRO, 2023)
To increase children's interest in the agricultural sector, a technology-basedapplicative learning method is needed in the field of agriculture for elementaryschool students through media-based educational videos on agriculture andindustrial form and hands-on practice of making entrepreneurial-type products.The purpose of this research is to describe the model of project-based learning(PjBL) with based education and industrial agriculture to increase students' skillsand creativity in the theme of entrepreneurship. The method used in this researchis a quasi-experimental design in the form of a non-equivalent control group design.The subjects of this research were 19 students in grade VI of SD Negeri Tempurejo1. The data analysis techniques used are the normality test, the homogeneity test,and hypothesis testing. Based on the research results, it can be concluded that themodel of project-based learning (PjBL) based on industrial agriculture canimprove students' creative thinking in class VI entrepreneurial theme learning.